Pandumaan-Sipituhuta Community Movement Action in Defense of Customary Forest Land Taking - Faisal Andri Mahrawa; Siregar, Endang SB; Adil Arifin (Journal of Peasants' Rights, 2022)
The Pandumaan-Sipituhuta indigenous peoples' social movements and disputes in defending their customary forest rights were impacted by the government's lack of transparency in identifying and determining concession rights, which resulted in a unilateral claim to the community's customary forest. This is the context for the Pandumaan-Sipituhuta indigenous community's social movement, which began in 2009, to achieve recognition and reclaim rights to their customary forest. A qualitative research method with descriptive-qualitative analysis was adopted. According to the study's findings, the community used a variety of techniques in their social movements, including warning letters, confiscation and burning of company equipment, rallies, and road closures. In addition to carrying out their movement actions, the community holds frequent deliberations in which all levels of society are involved to facilitate decision-making in their movement actions. Conflicts and obstacles confronting the community include the government's tardy response, which results in the community taking a long time to attain success. Finally, in February 2022, the community was legally recognized as a customary law community by the Humbang Hasundutan District Regulation Number 3 of 2019, and their rights to their customary forest were restored.